ETIKA PROFESI LEMBAGA KEJAKSAAN - Ahmad Habib Afandi; Rifki Hanif; Alifia Farhanah (JURNAL ILMIAH NUSANTARA, 2024)
The professional ethics of prosecutors were created so that prosecutors could be created who have integrity, are responsible, and are able to provide professional services to the community and are expected to be able to create a clean and effective bureaucracy, efficient, transparent based on Tri Krama Adhyaksa. Because everyone has recognition of fair legal guarantees, protection and certainty, as well as aqual treatment before the law. For this teason, by maintaining the prosecutor’s profession, it is hoped that prosecutors cn remain on a path that complies with the presence of a code of ethics all of this can be enforced in each profession.